Comparative risk for intracranial hemorrhage related to new oral anticoagulants: A network meta-analysis. Issue 12 (26th March 2021) - Ma, Tao; Liu, Chunbo; Jiang, Tianwei; Qin, Huaping; Wu, Ruhong; Zhou, Peng
Abstract: Background: The intracranial hemorrhage (ICH) risk of oral anticoagulants/non-vitamin K antagonist oral anticoagulants (NOACs) remains largely unknown. Patients who need oral anticoagulants such as aspirin or warfarin often suffer from obvious complications. Methods: This network meta-analysis intended to assess the ICH risk in patients taking NOACs. The data from PubMed, the Cochrane database, and Embase were reviewed. All phase III randomized controlled trials of NOACs (apixaban, edoxaban, dabigatran, rivaroxaban), aspirin and warfarin were reviewed. Results: Twenty-three trials involving 137, 713 participants were included, involving 6 regimens. Warfarin had the first risk of ICH (surface under the cumulative ranking area: 0.82), followed by dabigatran, edoxaban, aspirin, apixaban, rivaroxaban, and placebo. Dabigatran had the lowest risk of all-cause mortality (surface under the cumulative ranking area: 0.63), followed by apixaban, edoxaban, warfarin, rivaroxaban, aspirin, and placebo. Conclusion: Warfarin significantly increased the risk of ICH in patients taking oral anticoagulants compared with 4 NOACs (dabigatran, edoxaban, apixaban, rivaroxaban) and aspirin. Apixaban is least likely to induce all-cause mortality.